2019
DOI: 10.5540/tema.2019.020.02.381
|View full text |Cite
|
Sign up to set email alerts
|

Academic English Proficiency Assessment Using a Computerized Adaptive Test

Abstract: This paper describes the steps to convert a paper-and-pencil English proficiency test for academic purposes, consisting of multiple choice items administered following the Admissible Probability Measurement Procedure [24], adopted by the graduate program at the Institute of Mathematics and Computer Sciences at the University of São Paulo (ICMC-USP), Brazil, to a computerized adaptive test (CAT) based on an Item Response Theory Model (IRT). Despite the fact that the program accepts various internationally recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Compared to the average test length of the English Proficiency Test (EPT), which ranges from 65 to 75, administering the EPT in MCAT format caused approximately 60% to 65% decrements in test length since the average test length of the CAT version of EPT is equal to 28 with content balancing. This finding is supported by the study conducted by Curi and Silvia (2019) in which a 25-item test was considered sufficient enough to estimate the ability scores of candidates. Similarly, a test with 25 items on average in the context of CAT has been proposed by Van der Linden and Pashley (2010).…”
Section: Conclusion and Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Compared to the average test length of the English Proficiency Test (EPT), which ranges from 65 to 75, administering the EPT in MCAT format caused approximately 60% to 65% decrements in test length since the average test length of the CAT version of EPT is equal to 28 with content balancing. This finding is supported by the study conducted by Curi and Silvia (2019) in which a 25-item test was considered sufficient enough to estimate the ability scores of candidates. Similarly, a test with 25 items on average in the context of CAT has been proposed by Van der Linden and Pashley (2010).…”
Section: Conclusion and Discussionmentioning
confidence: 55%
“…Due to the adaptive nature of the measurement process of CAT designs, the very easy and difficult items are eliminated for each test-taker which decreases the test length and performance times (Curi & Silvia, 2019;Sukamolson, 2002). Thus, CATs are assumed to be advantageous compared to traditional paper-pencil exams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, isso pode causar um problema no balanceamento do conteúdo dos itens, conforme o examinado os responde, pode ser que ele tenha um comportamento que leve a responder itens repetidos do mesmo conteúdo, ou pode ser que um determinado conteúdo sequer seja apresentado em sua prova. Para contornar esse problema, seria ideal ter um banco de itens que satisfaça o propósito do teste, com conteúdo variado e com itens com níveis de dificuldades abrangentes, além de critérios e algoritmos de seleção que incorporem restrições baseadas em especificações pedagógicas (como conteúdo e exposição dos itens) (Silva et al, 2019).…”
Section: Teste Adaptativo Em Nível De Itemunclassified
“…Dimova et al (2020) have argued that locally developed language proficiency tests reflect institutional learning objectives, and may therefore be particularly well suited to fulfill important ancillary placement and diagnostic functions in language programs. However, researchers have commented on the high probability of misclassification involved in traditional PBTs and suggested that computer adaptive testing (CAT) may reduce misclassification by identifying the most informative items in an item bank to increase discrimination around cutoff points, and hence enhance the validity of test-based classification decisions (Curi & Silva, 2019; Mizumoto et al, 2019; Rudner & Guo, 2011; Zhang, 2010). The purpose of the current study is to investigate the potential application of CAT in this context by comparing the classification performance of CAT and paper-based testing (PBT) versions of an English language proficiency reading subtest developed and administered at a Turkish university.…”
mentioning
confidence: 99%